Coinciding SARS-CoV-2 infection in HIV patients with cerebral toxoplasma - Dika Chandra Bintari; Paulus Sugianto (School of Medicine, Universitas Syiah Kuala, 2021)
A massive and notorious impact of coronavirus disease 2019 (COVID-19) pandemic has affected communities worldwide, urging extra preventive measure, especially for individuals with comorbidities including those who are suffering from human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS). We reported a case of a 45-year-old man with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and HIV infection as well as toxoplasmosis. The patient presented to the hospital with decreased consciousness and stiffness on both hands and feet accompanied with loss of appetite, fever, and coughing. Since 2014, he had been diagnosed with HIV and undergone combined antiretroviral therapies. Toxoplasmosis was revealed by multislice computed tomography (MSCT) showing multiple rim-like lesion in cortex-subcortex of left temporal lobe along with surrounding perifocal oedema. Furthermore, the finding was corroborated by the contrasted image exhibiting rim enhancement patterns. The patient was also RT-PCR confirmed Covid-19. Following examinations, the patient received pyrimethamine with a loading dose of 200 mg. The management was continued with oral intake of pyrimethamine, clindamycin, folic acid, and vitamin B6 for maintenance dose. This case report suggests that HIV patient suffering from COVID-19 can be treated with antiretroviral therapies since the specific antivirus for SARS-CoV-2 has not yet available. We believe that this case report could contribute to more understanding on the development of clinical management for COVID-19 in HIV-positive patients.